Holoprosencephaly sequence with a constellation of anomalies in Yenagoa, a Niger Delta Region: report of two cases - Tunde-Oremodu II; Enefia KK; Idholo U; Ofure AO; Kunle-Olowu OE; Oyedeji A (Nigerian Journal of Paediatrics, 2024)
This report is on holoprosencephaly (HPE) sequence with other clinical and radiographic anomalies of other organs. This condition which has never been reported in Yenagoa, an oil rich Niger Delta Region was observed simultaneously in two neonates within a period of two months at different hospitals in this area. The inhabitants who include pregnant mothers with their fetuses are predisposed to health challenges associated with the exposure to toxic chemicals derived from environmental degradation and pollution due to oil spillage/processing. This report is therefore aimed at providing a description of HPE associated with varying multi-systemic conditions in order to motivate researches on prevalence of congenital anomalies and induce support in ensuring appropriate health care services. The approach to clinical evaluation and experience on diagnostic evidence is discussed. The importance of karyotyping which could not be carried out cannot be overlooked. However, the clinical and radiological features suggested the diagnoses of HPE Sequence. Holoprosencephaly (HPE) occurs due to a primary defect in prechordal mesoderm, resulting in fusion anomaly of the forebrain with also varying degrees of midline facial development anomalies. Although, HPE could be isolated, in certain conditions, it may occur in combination with other anomalies of the central nervous system and other organs. The causes of HPE are generally unknown but genetic and environmental factors have been implicated. Recognizing the prognosis in management, considerations vary from being conservative to reconstructive surgeries. The first neonate died on the 13th day of life, while the second neonate is still alive on supportive management of anticonvulsants and nutritional support on the 11th week of life at the time of writing this report.